PERBANDINGAN REFORMASI MANAJEMEN PUBLIK INDONESIA DAN PRANCIS - Lailatul Badriyah; Aminnullah (As-Sulthan Journal of Education, 2026)
This study examines public management reform in Indonesia and France using a comparative approach. The main focus of the study is to examine how the two countries responded to demands for improved public service quality, bureaucratic efficiency, and government digitalization within different socio-political contexts. Indonesia implemented bureaucratic reform after the 1998 Reformation as part of its democratization and governance reform process. Various initiatives, such as the implementation of a merit system, service digitalization, and performance evaluation, showed progress, but still faced structural and cultural obstacles. In contrast, France implemented reform through a more gradual and structured administrative modernization with a strong institutional foundation. The reforms in that country emphasized internal efficiency, policy consistency, and the strengthening of technology-based public services, despite also facing resistance from established institutions and labor unions. The comparative results demonstrate that public management reform cannot be separated from the national context. A successful reform model in one country cannot necessarily be applied in another without adjustments. Therefore, cross-national policy learning needs to consider administrative culture, institutional capacity, and the surrounding political conditions. This research is expected to enrich the literature on bureaucratic reform and provide a comprehensive overview for policymakers to design more adaptive and effective reforms.